Reconstruction of a large check and nose defect following excision of a basal cell carcinoma with squamous differentiation with cheek rotation flap and paramedian forehead flap in a patient with albinism - Boro, Sumanjit S.; Kakati , Kaveri (International Journal of Research in Medical Sciences, 2025)
Squamous differentiation of basal cell carcinomas are very aggressive tumors. The albino population on the other hand very much susceptible to radiation-induced skin changes and malignancies. Here we have presented a case of 34-year-old lady with large basal cell carcinoma of the cheek and lateral nose wall presented to us at a very late stage due to COVID-19-induced lockdown in this part of India. She was referred to the plastic surgery outpatient department (OPD) from the head and neck surgery for the reconstruction-related opinion. We excised the tumor with adequate margins and reconstructed the right cheek defect with the cheek rotation flap of size 15×14 cm and the right nose defect with a left paramedian forehead flap. The postoperative period was uneventful. After three weeks of the surgery, the flap division was done and one more week later, radiation therapy started. The patient was followed up at three monthly intervals at the OPD and she was doing fine till now and is also happy with the aesthetic appearance. For the large defects of the nose and cheek, a combination of cheek rotation flap and paramedian forehead flap can be done. Both are very reliable flaps and good color match and proximity to the defect made them an attractive option.